Образовательная эмиграция белорусов: социально-политические аспекты - Własiuk, Julia (Przegląd Wschodnioeuropejski, 2024)
The subject of the study is the problem of mass emigration of young people and students from the Republic of Belarus. The analysis of the current situation in Belarus, as well as the results of the survey of Belarusian students studying in Poland, show that a special role in the educational emigration of Belarusian youth is played not by economic factors, but more by political and social factors. Educational emigration subsequently turns into channels for Belarusian youth to leave for permanent residence. The country loses the future intellectual elite of society: highly educated people, future scientists, highly professional specialists in all spheres of the national economy. Emigration has acquired impressive scale, which leads to a huge crisis in Belarusian education and society as a whole. For receiving countries, educational migration serves as a tool to increase the country’s competitiveness in the world market.